Edukasi Bijak Finansial untuk Memperkuat Ketahanan Ekonomi Keluarga Nelayandi Desa Tapak, Kelurahan Tugurejo, Kota Semarang - Aulizza Abdul Fanni; Hapsari Ayu Kusumawardhani; Dea Adielyani (Universitas 17 Agustus 1945 Semarang, 2026)
The fishermen's community in Tapak Village, Tugurejo Subdistrict, Semarang faces persistent economic vulnerability driven by fluctuating income, low financial literacy, and exposure to illegal online lending and digital financial fraud. This community service program aimed to strengthen the economic resilience of fishermen's families through participatory financial literacy education. Using a participatory-interactive approach involving coastal community members, the program delivered comprehensive financial literacy training tailored to the needs of coastal communities. Program effectiveness was measured through pre-test and post-test instruments. Results showed significant improvements in participants' understanding of cash flow recording, ability to differentiate needs from wants, household budget planning, and capacity to identify illegal online lending characteristics. This program confirms that context-based participatory education is effective in enhancing the financial capacity and resilience of coastal communities.